Exclusion Through Inclusion. Struggles Over the Scalar Regimes of Belonging Europe and the Family at the 1995 Fourth UN World Conference on Women and the Agency of (Polish) Women - Ramme, Jennifer (Frontiers in Sociology, 2019)
Gender regimes of belonging are contextually variable and closely linked to other regimes of belonging, such as the family, the nation or the region. In the case of Poland, this contextuality and interdependence becomes apparent when analyzing struggles between feminist and Catholic anti-choice environments. While the first group opts for gender democracy, the other favors a familistic social order. In the mid-90s the struggle over “Polish” gender regimes took an international dimension and was played out as well at the international fora of the UN. When women’s rights actors from Poland appeared at the 4th World Conference on Women held by the UN in China in 1995, they experienced being positioned within a pre-structured spatial order and learned that this positioning and the synthesis within scalar regimes of belonging, such as the scale of family but also that of region, have a major impact on their political agency. The spatial order of the UN is a field of conflict, as certain positioning within regimes of belonging might limit political agency and therefore constrain the making of claims. NGOs struggle to get representation and definitional power over space and collective identity categories, but they also put efforts into changing the very composition and hierarchies within identity regimes. Toward this end, they form coalitions and networks and perform group identities and may even act in opposition to institutionalized regimes of belonging. The use of such concepts as belonging and scale allows us to avoid the analytical limits that are linked to the theoretical frameworks of recognition and identity politics. This article explores the strategies of scalar politics of belonging applied by NGOs, which also lead to the establishment of bodies representing women from the post-socialist countries of Central and Eastern Europe, such as the KARAT Coalition, but it also draws attention to the political effects of scaling belonging through the “family” or “Europe”. Today, the question as to what shape gender regimes of belonging should take is still an important site of struggle.